Nonclassical Measurement Error and Farmers’ Response to Information Reveal Behavioral Anomalies - Abay, Kibrom A. (World Bank, Washington, DC, 2022)
This paper reports on a randomized experiment conducted among Malawian agricultural households to study nonclassical measurement error in self-reported plot area and farmers’ responses to new information (the objective plot area measure) that was provided to correct nonclassical measurement error. Farmers' pre-treatment self-reported plot areas exhibit considerable nonclassical measurement error, most of which follows a regression-to-mean pattern with respect to plot area, and another 18 percent of which arises from asymmetric rounding to half-acre increments. Randomized provision of GPS-based measures of true plot area generates four important findings. First, farmers incompletely update mistaken self-reports; most nonclassical measurement error persists even after the provision of true plot area measures. Second, farmers update asymmetrically in response to information, with upward corrections being far more common than downward ones even though most plot sizes were initially overestimated. Third, the magnitude of updating varies by true plot area and the magnitude and direction of initial nonclassical measurement error. Fourth, the information treatment affects self-reported information about non-land inputs, such as fertilizer and labor, indicating that the effects of measurement error and updating spill over across variables. Nonclassical measurement error reflects behavioral anomalies and carries implications for both survey data collection methods and the design of information-based interventions.